The Correction of Multiple Diastemas in Adult Patients with Bad Tongue Habit (A Case Report): Koreksi Diastema Multipel dengan Kebiasaan Buruk Lidah pada Pasien Dewasa (Sebuah Laporan Kasus) - Sutan, Christinawaty; Sofyanti, Ervina (Dentika: Dental Journal, 2022)
There are various options in multiple diastemas correction due to the multifactorial malocclusion aetiology. The treatment of this malocclusion is a challenging task for clinicians not only for aesthetic achievement but also for the stability of orthodontic treatment. The multidisciplinary approaches depend on the aetiology of malocclusion and patient compliance. This reported case aims to describe the correction of multiple diastemas in adult patients with bad tongue habits. A 27-year-old male patient came to dental hospital Universitas Sumatera seekingrthodontics treatment with multiple spacing as the chief complaint. The comprehensive lateral cephalometry analysis showed class III skeletal malocclusion, concave profile skeletal trend, and abnormal dental inclination. There was also tongue thrusting in speech and swallowing based on functional examination. The initial orthodontic treatment was started by controlling the patient’s bad tongue habit along with orthodontic treatment. After seven-month of orthodontic treatment, this malocclusion was corrected and good interdigitation was achieved. Albeit there were no skeletal significant changes in this orthodontic treatment, the dental inclination showed a significant change based on cephalometry evaluation analysis. The success of the orthodontic treatment in the adult patient is not only dependent on proper mechanotherapy but also relied on the patient’s compliance with tongue habit control. Therefore, early bad oral habit detection as one of the etiologic factors in treating this malocclusion can support the success of orthodontic achievement.